Alterations in the Gut Microbial Composition and Diversity of Tibetan Sheep Infected With Echinococcus granulosus - Liu, Zhigang; Yin, Baishuang (Frontiers in Veterinary Science, 2022)
Hydatidosis/Cystic echinococcosis (CE) caused by Echinococcus granulosus is a parasitic zoonotic disease worldwide, threatening animal health, production and public health safety. However, it is still unclear that whether Echinococcus granulosus infection can result in the alteration of gut microbiota in Tibetan sheep. Therefore, a study was designed to investigate the influences of Echinococcus granulosus infection on gut microbiota of Tibetan sheep. A total of ten ovine small intestinal contents (five from healthy and five from infected) were obtained and subjected to high-throughput sequencing by MiSeq platform. A total of 239,5641 sequences and 585 operational taxonomic units (OTUs) were identified. Firmicutes and Proteobacteria were the most dominant phyla in all samples. Moreover, the proportions of Armatimonadetes and Firmicutes in the infected Tibetan sheep were significantly decreased, whereas Actinobacteria, Chloroflexi and Acidobacteria had significantly increased. At the genus level, Christensenellaceae_R-7_group and Ruminococcaceae_NK4A214_group were the predominant bacterial genera in all the samples. Furthermore, the healthy Tibetan sheep exhibited higher abundances of Intestinimonas, Butyrivibrio, Pseudobutyrivibrio, Ruminococcaceae, Eubacterium_coprostanoligenes_group, Oxobacter, Prevotella_1, Ruminiclostridium_6, Coprococcus_1, Ruminococcus, Lachnospiraceae_UCG-002, Olsenella and Cetitomaculum, whereas Kocuria, Clostridium_sensu_stricto_1, Slackia, Achromobacter and Stenotrophomonas levels were lower. In conclusion, our results conveyed an information that Echinococcus granulosus infection may cause an increase in pathogenic bacteria and a decrease in beneficial bacteria. Additionally, a significant dynamical change in gut microbiota could be associated with Echinococcus granulosus infection.